Effect of spiritual emotional freedom technique on blood glucose in type 2 diabetes patients: A Quasi-experimental study - Harwina Widya Astuti; Sri Hunun Widiastuti; Nawang Pujiastuti; Imas Mulyani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Diabetes mellitus (DM) is a chronic metabolic disorder characterized by impaired insulin function leading to hyperglycemia. Psychological stress and anxiety may exacerbate glycemic dysregulation. Complementary therapies such as the Spiritual Emotional Freedom Technique (SEFT) have been proposed to address both psychological and physiological aspects of DM. This study aimed to determine the effect of SEFT on blood glucose levels among patients with type 2 diabetes mellitus. Research Methodology: This study employed a quasi-experimental design with a pretest–posttest control-group design. A total of 30 participants were recruited using purposive sampling and allocated into an intervention group (n=15) and a control group (n=15). The intervention group received SEFT therapy, while the control group received standard care. Blood glucose levels were measured before and after the intervention. Data were analyzed using a paired t-test for within-group comparisons and an independent t-test for between-group differences, with a 95% confidence interval (CI). Results: In the intervention group, there was a significant reduction in blood glucose levels after SEFT therapy (mean difference = 8.01; 95% CI: 2.22–13.22; p=0.016). In contrast, the control group showed no significant change (mean difference = −2.55; 95% CI: −5.69–0.51; p = 0.071). Between-group analysis revealed a statistically significant difference in post-intervention blood glucose levels (mean difference = 17.61 vs 10.62; p = 0.03), indicating the effectiveness of SEFT. Conclusion: SEFT therapy significantly reduces blood glucose levels in patients with type 2 diabetes mellitus. This intervention may serve as a complementary non-pharmacological strategy to improve glycemic control by addressing psychological stress. Integration of SEFT into diabetes management programs is recommended